Fiscal federalism and economic growth - Jan Keith Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper uses an endogenous-growth model with overlapping generations to explore the connection between fiscal federalism and economic growth. The analysis shows that federalism, which allows public-good levels to be tailored to suit the differing demands of young and old consumers, who live in different jurisdictions, increases the incentive to save. This stronger incentive in turn leads to an increase in investment in human capital, and a byproduct of this higher investment is faster economic growth.
Keywords: H70; H10; 330; Finanzföderalismus; Wirtschaftswachstum; Neue Wachstumstheorie; Sparen; Bildungsinvestition; Theorie